Paolo Fabbri’s Pinocchio – with an appendix containing an unpublished text by Paolo Fabbri titled "Structural Analysis of Pinocchio" - Traini, Stefano (E|C, 2025)
Paolo Fabbri has dealt with Pinocchio over the years on several occasions, showing a passion for Collodi’s puppet that bordered on obsession. In this article I try to reconstruct Paolo Fabbri’s studies on Pinocchio, highlighting on the one hand the recurring themes and the main interpretative lines, on the other the tools used and the methodological choices. The work was also carried out by consulting the materials collected by Fabbri, now preserved at the “Paolo Fabbri” Library in Palermo, in Palazzo Tarallo.